2022
DOI: 10.3390/horticulturae8010044
|View full text |Cite
|
Sign up to set email alerts
|

Low CO2 Levels Are Detrimental for In Vitro Plantlets through Disturbance of Photosynthetic Functionality and Accumulation of Reactive Oxygen Species

Abstract: Photosynthesis of plantlets in tissue culture containers is not considered important, compared to photosynthesis of ex vitro plants, due to the exogenous source of carbohydrates present in tissue culture media. However, CO2 starvation can generate a burst of reactive oxygen species (ROS). We examined this phenomenon in tissue culture, since CO2 levels may become very low during the light period. The research was carried out with lily scales, regenerating adventitious bulblets, and with Arabidopsis seedlings. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In the photomixotrophic system with a lower gas exchange rate (or without natural ventilation), the microenvironment of the flask is the factor with the greatest influence on the growth and development, since carbon is made available through the supply of sucrose in the medium [33][34][35]. Undeniably, sealing the bottles (rigid lids or without membranes) provides high humidity inside them, greater accumulation of the phytohormone ethylene, reduced gas exchange, and low CO 2 concentration [36][37][38][39]. These factors lead to the development of plants with morphophysiological disorders, such as leaf formation displaying mesophyll with large intercellular spaces, poorly developed vascular system, lack of epicuticular wax formation, and non-functional stomata [16,18,19,40].…”
Section: Discussionmentioning
confidence: 99%
“…In the photomixotrophic system with a lower gas exchange rate (or without natural ventilation), the microenvironment of the flask is the factor with the greatest influence on the growth and development, since carbon is made available through the supply of sucrose in the medium [33][34][35]. Undeniably, sealing the bottles (rigid lids or without membranes) provides high humidity inside them, greater accumulation of the phytohormone ethylene, reduced gas exchange, and low CO 2 concentration [36][37][38][39]. These factors lead to the development of plants with morphophysiological disorders, such as leaf formation displaying mesophyll with large intercellular spaces, poorly developed vascular system, lack of epicuticular wax formation, and non-functional stomata [16,18,19,40].…”
Section: Discussionmentioning
confidence: 99%
“…It is challenging for in vitro plantlets to survive ex vivo due to their aberrant morphology, anatomy, and physiology [152,[166][167][168]. Tissue-cultured plants are unlikely to be actively photosynthesizing, despite the fact that they might appear normal in vitro [169]. Due to the persistence of pathogenic microorganisms, conventional vegetative propagation in bulbous crops like gladiolus can result in phytopathological and physiological deterioration; epigenetic changes are the cause of physiological deterioration [170,171].…”
Section: Difficulty and Challengesmentioning
confidence: 99%
“…Improper development of the photosynthetic system and malfunctioning of stomata during in vitro culture may lead to a series of morphological and physiological disorders of plant tissue (Urban et al, 2017). Although tissue-cultured plants may look normal in vitro, they are unlikely to be actively photosynthesizing (Askari et al, 2022). This is due to the provision of sucrose as the source of carbon and different environments than ex vitro, which disturb the natural development of the photosynthetic apparatus and stomatal responses afterward (Gago et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is wrongly claimed that due to the presence of sugar in the medium, in vitro, plants do not need photosynthesis. It has been shown that the removal of light and CO 2 as the two main inputs of photosynthesis is harmful for the growth of tissue cultured plants (Askari et al, 2022). Adaptation of plantlets after in vitro growth needs practices such as reducing RH, increasing light level, and CO 2 concentration, or reducing the osmotic potential of the culture medium (Aliniaeifard et al, 2020).…”
Section: Introductionmentioning
confidence: 99%